A6_6 Venusian Vacation - Schulz, William; Doyle, Patrick; Heaps, Jonathan; Minnis, Eden (Physics Special Topics, 2017)
In this paper, we investigated the conditions required to ensure human survival on Venus, along with the effects of the Venusian climate on the astronauts and the spacecraft. By considering thermal conductivity and Young's modulus, we calculated that 78 MW of power would be required to maintain a room temperature environment within the spacecraft, a human would last 47.5 s before succumbing to the high temperatures, and that Tungsten would be required to prevent a spacecraft from breaking due to thermal expansion.